HSATII RNA-dependent triplex formation in early human embryogenesis as a potential mechanism for Y chromosome loss in Turner syndrome - Fularski, Krystian (Frontiers in Molecular Biosciences, 2025)
Turner syndrome (TS) arises from partial or complete loss of a sex chromosome, yet the mechanistic basis for Y chromosome loss (LoY), which may contribute to a subset of TS cases, remains unclear. This article addresses the existing gap in knowledge by proposing a hypothesis linking a transient physiological window of elevated HSATII RNA levels during preimplantation embryogenesis to recent bioinformatic predictions indicating that Y-linked HSATII arrays possess uniquely high triplex-forming propensity. In this context, HSATII-derived RNAs could form RNA-DNA triplexes in early embryogenesis preferentially at Y-linked HSATII tracts. If unresolved, these structures may stall replication forks and promote Y chromosome instability which may ultimately lead to complete or partial LoY. The proposed model reframes part of the TS etiology from a stochastic segregation error toward a definable process, and motivates experimental validation of its predictions. If supported by experimental evidence, this framework could further guide the search for modifying factors - such as interindividual variation in the Y-linked HSATII sequence or triplex-resolution efficiency - and, in the longer term, enable risk stratification for Y chromosome instability in potential embryos based on parental molecular profiles. In a broader context, the hypothesis underscores pericentromeric satellite biology as a potentially underexplored contributor to genome stability in early human development.